Impact of Neurofascin on Chronic Inflammatory Demyelinating Polyneuropathy via Changing the Node of Ranvier Function: A Review - Gao, Ying; Kong, Lingxin; Liu, Shan; Liu, Kangding; Zhu, Jie (Frontiers in Molecular Neuroscience, 2021)
The effective conduction of action potential in the peripheral nervous system depends on the structural and functional integrity of the node of Ranvier and paranode. Neurofascin (NF) plays an important role in the conduction of action potential in a saltatory manner. Two subtypes of NF, NF186 and NF155, are involved in the structure of the node of Ranvier. In patients with chronic inflammatory demyelinating polyneuropathy (CIDP), anti-NF antibodies are produced when immunomodulatory dysfunction occurs, which interferes with the conduction of action potential and is considered the main pathogenic factor of CIDP. In this review, we describe the assembling mechanism and anatomical structure of the node of Ranvier, as well as the necessary cell adhesion molecules for its physiological function. The main points of the review are that we summarized recent studies on the role of anti-NF antibodies in the changes in the node of Ranvier function and its impact on clinical manifestations, as well as analyzed the possible mechanisms underlying the pathogenesis of CIDP.